Quando avere un lavoro non basta a proteggere dalla povertà - saraceno, chiara (Lectio Magistralis, 2020)
Having a job is not always a guarantee against poverty, for oneself and one's family. This depends on the one hand on the level of income acquired through work, on the other hand on the worker's family situation. While a low income does not always lead to poverty in terms of consumption - if the worker's family is able to provide additional incomes - on the contrary, an average income may not be sufficient if it is the only one in a family compose by several members. Low or intermittent work incomes, on the one hand, and high incidence of single-income families on the other hand - especially if they count several children - are among the main causes of poverty despite a work income. Above all, the second phenomenon explains why Italy is among the European countries with a relatively high percentage of poor workers on a family basis, a condition which is also the cause of a high incidence of child poverty.